2020
DOI: 10.1371/journal.pone.0243578
|View full text |Cite
|
Sign up to set email alerts
|

Novel computer-based assessments of everyday visual function in people with age-related macular degeneration

Abstract: Purpose To test the hypothesis that the performance in novel computer-based tasks of everyday visual function worsens with disease severity in people with non-neovascular age-related macular degeneration. Methods Participants with and without non-neovascular age-related macular degeneration (≥60 years, minimum logMAR binocular visual acuity 0.7) performed a series of standard visual function tests and two novel computer-based tasks. In a visual search task, participants had to locate an image of a single rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Participants with GA recorded slower response times than other groups for performing visual searches for everyday objects and had fewer correct responses; >50% performed outside the normal limit for task performance. 30 However, visual and reading acuity do not necessarily reflect functional reading ability in patients with GA and may depend on the location of atrophy. 31 , 32 Sunness et al 31 conducted a study of 156 US patients with GA who had visual acuity of 20/50 or better (logMAR visual acuity <0.46) in one or both eyes with GA to explore reading difficulties and the progression of reading impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Participants with GA recorded slower response times than other groups for performing visual searches for everyday objects and had fewer correct responses; >50% performed outside the normal limit for task performance. 30 However, visual and reading acuity do not necessarily reflect functional reading ability in patients with GA and may depend on the location of atrophy. 31 , 32 Sunness et al 31 conducted a study of 156 US patients with GA who had visual acuity of 20/50 or better (logMAR visual acuity <0.46) in one or both eyes with GA to explore reading difficulties and the progression of reading impairment.…”
Section: Resultsmentioning
confidence: 99%
“…About one-half of patients develop GA in both eyes within seven years of initial diagnosis [4]. People with GA have worse vision-related quality-of-life even when their visual acuity is preserved; for example, we have shown that they have increased anxiety about mobility, problems with searching for objects and difficulty recognising faces [5][6][7][8][9]. With no current treatment for GA, patients diagnosed in hospital eye service are typically discharged to the community for monitoring [10,11].…”
Section: Intravitreal Treatment For Geographic Atrophy: Coming Soon To a Patient Near You?mentioning
confidence: 99%
“…Loss of vision due to AMD has been found to have numerous effects on people, such as negatively affecting mental health [9] and making daily activities more difficult, often leading to a decrease in physical activity levels and an overall poorer quality of life [10]. It can also be quite isolating, with many of those with the condition reporting that it prevents them from independently reaching local amenities [3].…”
Section: Introductionmentioning
confidence: 99%